Race and Arab Americans before and after 9/11 : (Syracuse University Press, 2008)
Bringing the rich terrain of Arab American histories to bear on conceptualizations of race in the U.S., this groundbreaking volume fills a critical gap in the field of ethnic studies. Unlike most immigrant communities who either have been consistently marked as non-white, or have made a transition from non-white to white, Arab Americans historically have been rendered white and have increasingly come to be seen as non-white. matters to the study of Arab American histories and asks essential questions.